2021
DOI: 10.3389/fonc.2021.731414
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome Analysis Reveals the Impact of Photodynamic Therapy on Cerebrovascular Endothelial Cells

Abstract: Blood vessels in the brain tissue form a compact vessel structure and play an essential role in maintaining the homeostasis of the neurovascular system. The low dosage of photodynamic intervention (PDT) significantly affects the expression of cellular biomarkers. To understand the impact of photodynamic interventions on cerebrovascular endothelial cells, we evaluated the dosage-dependent impact of porfimer sodium-mediated PDT on B.END3 cells using flow cytometer, comet assay, RNA sequencing, and bioinformatics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The target genes ESPL1, KDM6A, and BCORL1 may be engaged in reproductive processes. In many previous studies, ESPL1 (extra spindle pole bodies like 1) have been found involved in cellular mitosis and cell cycle process ( 45 47 ). KDM6A (lysine demethylase 6A) belongs to the KDM6 family of histone H3 lysine 27 (H3K27) demethylases, which is an X- linked protein that contains a catalytic Jumonji C (JmjC) domain can facilitate the removal of the methyl group on di- and trimethylated H3K27 (H3K27me2/3), it can not only manifest demethylase activity but also regulate gene expression and enhancer activation independently of its demethylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…The target genes ESPL1, KDM6A, and BCORL1 may be engaged in reproductive processes. In many previous studies, ESPL1 (extra spindle pole bodies like 1) have been found involved in cellular mitosis and cell cycle process ( 45 47 ). KDM6A (lysine demethylase 6A) belongs to the KDM6 family of histone H3 lysine 27 (H3K27) demethylases, which is an X- linked protein that contains a catalytic Jumonji C (JmjC) domain can facilitate the removal of the methyl group on di- and trimethylated H3K27 (H3K27me2/3), it can not only manifest demethylase activity but also regulate gene expression and enhancer activation independently of its demethylase activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ALA-PDT can lead to both down-regulation of NF-kB and enhanced its activation in glioma cells [189,192,193]. Moreover, low-dose PDT with PS Porfimer sodium induces NF-kB of TNF-a/NF-kB pathway in cerebral vascular endothelial cells, and impairment of their function [194]. This effect may be important for the effectiveness of delivering other therapeutics to the tumor after PDT.…”
Section: Nuclear Factor Kbmentioning
confidence: 99%
“…The clinical reports suggest that the PDT intervention may significantly stimulate the endothelial cells of the blood-brain barrier (BBB) for specific responses. Identifying and exploring the pivotal changes in endothelial cells after PDT intervention may provide necessary information to guide the clinical application of PDT on GBM therapy [5]. The study investigated the temporary opening of BBB due to PDT [6,7], initiation of an immune response against tumor cells [8][9][10], and deactivation of tumorassociated macrophages that promote tumor progression [11].…”
Section: Introductionmentioning
confidence: 99%